PSIKOLOGI TRANSPERSONAL, DISCOURSE IMPLEMENTATIF DALAM MEMBANGUN KARAKTER - Shifa Rifkiana; Subaidi (Risalah, Jurnal Pendidikan dan Studi Islam, 2022)
The problem of this study, begins with the uncharacterizing of an individual. Why? It may be that it only focuses on one intelligence (IQ, EQ, or SQ). To discuss the matter, the aim of this study is to know implementation of character in general and from a view of transpersonal psychology transpersonal psychology is not only interested in issues that are commonly studied by mainstream psychology, such as personality, emotion, cognition, or intelligence. Transpersonal psychology deals with problems such as overture, trance, altered consciousness, mysterious experiences, and spiritual undergrowth. This research a kualitative methods for this type of literature benellian, which is followed by descriptive and qualitative analysis.